Roles of endogenous retroviruses in early life events - Magiorkinis, G; Katzourakis, A; Lagiou, P (Cell Press, 2017)
A retrovirus that infected our ancestors 100 million years ago became a human gene that is expressed in embryos and cancers, and can be detected in the blood of pregnant women. Accumulating evidence suggests potential roles for endogenous retroviruses in early life events, which may affect adult health.